2017
DOI: 10.1038/s41598-017-03572-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mass spectrometry analysis revealed a role for glucosamine in potentiating recovery following desiccation stress in Chironomus

Abstract: Desiccation tolerance is an essential survival trait, especially in tropical aquatic organisms that are vulnerable to severe challenges posed by hydroperiodicity patterns in their habitats, characterized by dehydration-rehydration cycles. Here, we report a novel role for glucosamine as a desiccation stress-responsive metabolite in the underexplored tropical aquatic midge, Chironomus ramosus. Using high- throughput liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF-MS) analysis, biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 94 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…Nevertheless, aquatic insects experience less variation in their thermal environment than terrestrial insects, therefore, it is not surprising that aquatic insects are more sensitive to heat stress. Furthermore, desiccation affects aquatic Chironomid midge larvae more than the terrestrial Drosophilid larvae as is reported earlier by Thorat et al (2017).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Nevertheless, aquatic insects experience less variation in their thermal environment than terrestrial insects, therefore, it is not surprising that aquatic insects are more sensitive to heat stress. Furthermore, desiccation affects aquatic Chironomid midge larvae more than the terrestrial Drosophilid larvae as is reported earlier by Thorat et al (2017).…”
Section: Resultssupporting
confidence: 66%
“…Often, organisms exhibit specific patterns of adaptations in response to these environmental stresses (Bijlsma and Loeschcke 2005;Davies et al 2014). In this context, insects are suitable model systems for determining the responses to environmental stress (Datkhile et al 2015;Thorat et al 2016Thorat et al , 2017. This is because in spite of being small and having a high metabolic rate, insects are among the most widely distributed animals and occur in almost all of the habitats in the biosphere and as a consequence are adapted to cope with a wide range of environmental stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Glucosamine has also been reported to increase the life span of Caenorhabditis elegans and ageing mice through glycolysis impairment 7 . A participation of the amino sugar in the recovery from desiccation of Chironomus ramosus larvae has been recently discovered 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The midges form an abundant macroinvertebrate insect group of aquatic ecosystems and serve as food source for organisms in both aquatic and terrestrial habitats (Oliver, 1971). Chironomid midges are known to be extremely robust insects and recently, their impressive pliability to combat fluctuations in hydroperiodicity patterns have made them a popular model system for elucidating the consequences associated with climate change stressors such as temperaturehumidity imbalance (Walker et al, 1991;Larocque et al, 2001;Gusev et al, 2011;Cornette and Kikawada, 2011;Lee and Denlinger, 2015;Thorat and Nath, 2016;Thorat et al, 2017;Belle et al, 2017;Oppold et al, 2017).…”
Section: Chironomid Biology: Brief Overviewmentioning
confidence: 99%
“…Recently, Sutherland et al (2006) described a pathway for the evolution of silk genes in honey bees, while Yonemura et al (2006) demonstrated homology between trichopteran silk from aquatic caddis fly larvae with lepidopteran silk. Underwater silk-woven housing nests in Chironomus is a result of the tubicolous nature of larval midges and has often been associated with its remarkable resilience to a variety of environmental stressors, especially drought-induced photo-oxidative damage (Watanabe et al, 2004;Watanabe, 2006;Thorat and Nath, 2015;Thorat and Nath, 2016; Thorat and B.B. Nath 2017).…”
Section: Introductionmentioning
confidence: 99%